Modeliranje poplavljanja urbanih območij - Rak, Gašper (Acta hydrotechnica, 2018)
The impact of flooding is significantly greater in urban areas than in rural environments, as the exposure and value of property and the likelihood of endangering human lives is higher. There is therefore a great need for hydraulic models, which can predict the direction and extent of flooding. Buildings pose obstacles to water flow, considerably affecting its course, wherefore buildings should be taken into account in hydraulic models. This study compared two different ways of taking account of buildings in mathematical hydraulic models. The first approach models buildings by increasing the value of the hydraulic roughness coefficient for building footprints, while the second approach includes buildings in a digital terrain model at their locations. We also analysed the sensitivity of modelling results in respect of the cell size of the computational mesh, which can significantly affect the results of hydraulic model. Hydraulic analysis was carried out with 2D model for area of Gornja Radgona, which would be the flood of the Mura River in the event a part of flood protection wall collapsed. The impact of cell size and the approach of modelling buildings on the run-off regime and flood.
Keywords: buildings modelling; flood hazard; hidravlično modeliranje; hidrotehnika; hydraulic engineering; hydraulic modelling; modeliranje objektov; poplavna nevarnost; urban areas; urbane površine